Tradisi Bele Kampung Masyarakat Desa Igal Kecamatan Mandah Kabupaten Indragiri Hilir Riau (Kajian Normatif dan Historis) - Muhammad Sayuti; Agung Setiabudi (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
This article is motivated by the existence of a unique activity that is routinely carried out every year, precisely in the month of Muharram, this activity has become a tradition which is named by the local community as bele kampong. This article aims to look at the bele kampong tradition from an Islamic perspective using a normative and historical approach. The research approach used is a qualitative approach with case studies research type. The results of the research show that historically this tradition was carried out by the chief prince of Igal village, which was caused by some people being disturbed by spirits (jinn). Apart from that, people also often saw large yellow crocodiles in the village. Normatively, this tradition is not said to be violates Islamic law as long as you don't ask for help from other than Allah SWT.